Peptide-mimetics derived from leucyl-tRNA synthetase are potential agents for the therapy of mt-tRNA related diseases - Pisano, Annalinda; Belloli, Sara; Pignataro, Maria Gemma; Rainone, Paolo; Valtorta, Silvia; Coliva, Angela; de Turris, Valeria; Mosca, Luciana; Di Micco, Patrizio; Moresco, Rosa Maria; d’Amati, Giulia; Morea, Veronica (Frontiers in Pharmacology, 2025)
IntroductionMitochondrial diseases caused by point mutations in mitochondrial tRNA (mt-tRNA) genes, including MELAS and MERRF syndromes, represent a significant unmet clinical need, due to the lack of effective treatments. We previously identified peptide molecules derived from human leucyl-tRNA synthetase, whose features make them attractive leads for the development of therapeutic agents against mt-tRNA point mutations-related diseases. Indeed, we demonstrated that, upon exogenous administration, these peptides penetrate human cell and mitochondrial membranes; stabilize mitochondrial tRNA structures; and rescue severe mitochondrial defects in cells bearing the point mutations m.3243A>G and m.8344A>G, responsible for MELAS and MERRF syndromes, respectively.ResultsTo progress towards therapeutic applications, in this work we designed three peptide-mimetic derivatives (PMTs). These are composed entirely of D-amino acids and potentially endowed with enhanced stability in human plasma and resistance to enzymatic degradation. We show that, like the parent peptide, the PMTs have mitochondrial localization and improve cell viability and oxygen consumption in human cybrid cell lines bearing the aforementioned point mutations. Additionally, as anticipated, the PMTs had significantly higher plasma stability than the parent peptide. The most promising PMT was radiolabelled with Cu-64 and used in in vivo biodistribution and tolerability studies. Importantly, i. v. administered PMT reached all body districts, including heart, muscle and even brain, thus revealing an intrinsic ability to cross the blood-brain barrier. Finally, PMT was safe in adult wild-type mice at dosages up to 10 mg/kg.DiscussionThese findings represent a significant step towards the implementation of therapeutic strategies for mttRNA-related mitochondrial diseases.